THE IMPLEMENTATION OF INTERNET-BASED PROJECT WORK IN WRITING CLASS TO ENHANCE STUDENTS’ CRITICAL THINKING - Nety Herawati (Journal of English Education Program (JEEP), 2015)
This paper reports on the implementation of Internet-based Project Work in writing class to enhance students' critical thinking. This study is aimed at finding out the implementation of Internet-based Project Work in writing class to enhance students' critical thinking, the teacher's perceptions toward the implementation of Internet-based Project Work in writing class to enhance students' critical thinking, and the students' perceptions toward the implementation of Internet-based Project Work in writing class to enhance their critical thinking. This study employed a qualitative research that was designed as a case study design. The writer took the eleventh grade students of senior high school in a science class in one of Senior High School in Ciamis that consisted of 39 students and an English teacher as a sample purposively. The data were collected through several instruments, including classroom observation, interview, and questionnaire. The findings based on first purpose of the study revealed that the implementation of Internet-based Project Work in writing class to enhance students' critical thinking used several steps; choosing the topic, making the task clear, finding the resource, and deciding on the outcome. Based on these findings, it is recommended that Internet-based Project Work is implemented in writing class to enhance students’ critical thinking. However, the teacher should keep monitoring the students’ activities while implementing Internet-based Project Work in order that the students do not use the Internet for something out of context of teaching and learning activities.